Integrated science - Tillery, Bill W. ([Boston] : McGraw Hill Education, 2004)
Integrated science is a straight forward, easy-to-read, but substantial introduction to the fundamental behavior of matter and energy in living and nonliving systems. It is intended to serve the needs of nonscience majors who are not required to complete one or more science courses as part of a general or basic requirements.
Chapter1. What is science -- Chapter2. Motion -- Chapter3. Energy -- Chapter4. Heat and temperature -- Chapter5. Wave motions and sounds -- Chapter6. Electricity -- Chapter7. Light -- Chapter8. Atoms and periodic properties -- Chapter9. Chemical reactions -- Chapter10. Water and solutions -- Chapter11. Nuclear reactions -- Chapter12. The universe -- Chapter13. The solar system -- Chapter14. The earth -- Chapter15. The earth's surface -- Chapter16. Earth's weather -- Chapter17. Earth's waters -- Cha[pter18. Organic and biochemistry -- Chapter19. The nature of living things -- Chapter20. The origin and evolution -- Chapter21. The history of life on earth -- Chapter22. Ecology and environment -- Chapter23. Human biology: Sex and nutrition -- Chapter24. Human biology: Materials exchange and control -- Chapter25. Mendelian and molecular genetics .
Includes index.
Keywords: SCIENCE